Thank you for the opportunity to help you with your question!
[1/ (1+sint) ] +[1/ (1-sint)]
=[1/ (1+ sint) * ((1- sint) / (1- sint) )] +[1/ (1- sint) ((1+ sint) / (1+ sint) )]
=[(1-sint ) / (1- sin^2 t))] +[(1+sint) / (1- sin^2t) ]
=[(1-sint ) / cos^2t )] +[(1+sint) / (cos^2t ) ] as Cos^2t = 1- sin^2t
=[(1-sint ) + (1+sint )/ cos^2t )]
=[(1-sint + 1+sint )/ cos^2t )]
=[(2 )/ cos^2t )]
=2 sec^2t answer as 1/cos^2t = sec^2t
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?